KERAGAAN MAKROZOOBENTOS SEBAGAI BIOINDIKATOR KUALITAS AIR DI BAGIAN HILIR SUNGAI HURUN LAMPUNG - Vina Triesa Putri; Nidya Kartini; Indra Gumay Yudha; Abdullah Aman Damai (Jurusan Akuakultur, Universitas Bangka Belitung, 2021)
Macrozoobenthos is one of the organisms that can be used as biological indicators because it tends to live in an area and has sensitivity to environmental changes. The Hurun River had many community activities. Based on this, it was necessary to analyze the diversity of macrozoobenthos which will be compared with the physical and chemical parameters of water in order to find out the indicators that affect the abundance of macrozoobenthos in the river. The purpose of this research was to determine the macrozoobenthic community structure which found in the Hurun River based on diversity, uniformity and dominance indices, to build multiple linear regression models, and to determine the bioindicators of pollution in the Hurun River. The factors that influence the abundance of macrozoobenthos are temperature, depth, brightness, DO, TOM, and salinity. The types of macrozoobenthos obtained were 87 species with the highest abundance of macrozoobenthic animals of 70,666.56 ind/m3 while the lowest abundance of macrozoobenthic animals was 13,000.96 ind/m3. Based on data analysis, the macrozoobenthic diversity index was included in the medium category, the level of macrozoobenthic uniformity was included in the high, medium, and low categories, and the dominance level which was included in the medium and low categories. Multiple regression models with a confidence level of 5% get R2 results of 0.86. The level of pollution that occured in the Hurun River based on bioindicators with the ABC curve shows moderately polluted.